Поховання 472 нетайлівського могильника салтівської культури - Аксьонов, В.С. (Археологія, 2011)
Публікація подає матеріали одного з поховань Нетайлівського могильника салтівської культури, котре містило імітацію золотого візантійського соліда. Представлены материалы погребения 472 Нетайловского могильника салтовской культуры (Волчанский рн Харьковской обл.). Погребальный инвентарь захоронения, представленный серебряными элементами поясной гарнитуры (пряжка, 13 поясных бляшек, наконечник пояса) и имитацией золотого византийского солида Льва III, чеканеного в 732—741 гг., дает представление о начальном сложении материальной культуры салтовского населения в бассейне Северского Донца. За составом инвентаря погребение следует датировать последней четвертью VIII в., вероятно, 770—790 гг. Materials of burial 472 at Netaylivskyi burial ground of Saltivska culture are presented (Vovchansk Region of Kharkiv Oblast). Funeral inventory of the tomb is represented by silver elements of belt set (a buckle, 13 belt plates, and a belt ending) and by an imitation of golden Byzantical solidus of Leo III minted from 732 to 741. The inventory gives an idea of an initial development of material culture of Saltivska culture population inhabiting the basin of the Siverskyi Donets River. According to the composition of inventory the burial should be dated by the last quarter of the 8th c., apparently by the period from 770 to 790.